The three dimensions of headache impact: pain, disability and affective distress - Holroyd, Kenneth A. (1999)
It is increasingly recognized that pain measures alone provide incomplete information about the impact of pain on functioning or quality-of-life. A wide range of measures that promise to provide additional information about the impact of pain on people's lives are thus coming into use. In order to clarify the construct of headache impact, we attempted to identify the dimensions assessed by a set of 22 headache-impact measures and to identify the specific measures that best assessed each of these headache-impact dimensions. Adults (n = 329) with frequent benign headache disorders completed a comprehensive assessment battery that included 22 headache-impact measures. Factor analysis was then used to identify dimensions underlying the headache-impact measures. Three factors labeled Affective Distress, Pain Density and Disability best accounted for correlations among headache-impact measures. Interfactor correlations ranged between 0.37 and 0.20, suggesting three correlated but separable impact dimensions. These results suggest the construct of headache impact needs to be broadened beyond pain and disability to include affective distress. An adequate assessment of the impact of recurrent headache disorders in clinical trials and other research may require measures from all three of the headache-impact dimensions identified here.